Effect of supernatant water level on As removal in biological rapid sand filters - Gude, J.C.J. (2021)
The increase in supernatant level from 5 to 120 cm resulted in additional HFO production prior to rapid filtration (1.5, 5 and 10 m/h), i.e. homogeneous Fe(II) oxidation and flocculation, and subsequently, HFO ending up deeper into the filter bed (120 cm filter depth). At a low supernatant water level of 5 cm, Fe(II) oxidised heterogeneously and was removed within the top 20 cm of the filter bed. Consequently, filters with high supernatant levels removed As to lower levels (by 20%) than in filters with low supernatant water levels. The benefits of Fe(II) oxidation prior to filtration for As removal was confirmed by comparing Fe(III) to Fe(II) additions in the supernatant water or in the filter bed. Overall it is concluded that in biological groundwater filters, the combination of a higher supernatant level and/or Fe(III) addition with biological As(III) oxidation in the top of the filter bed promotes As removal.